Comparing the Agency of Hybrid Meeting Remote Users in 2D and 3D Interfaces of the Hybridge System - Spittle, Becky; Panda, Payod; Tankelevitch, Lev; Inkpen, Kori; Tang, John; Junuzovic, Sasa; Qi, Qianqian; Sweeney, Pat; Wilson, Andrew D.; Buxton, Bill; Sellen, Abigail; Rintel, Sean (CHI EA 2024, 2024)
Hybridge is an experimental system for exploring the design of remote inclusion for hybrid meetings. In-room users see remote participants on individual displays positioned around a table, and remotes see video feeds from the room integrated into a digital twin of the meeting room. Remotes can choose where to appear in and view the meeting room from. We designed two digital interfaces for remote attendees, one using a 2D canvas, and the other using a 3D digital twin of the room as the medium of interaction. To decide which interface to use for future evaluation, we conducted a within-subjects comparison of 24 groups completing survival tasks. We found that 3D outperformed 2D in the participants’ perceived sense of awareness, sense of agency, and physical presence. Majority of participants also subjectively preferred 3D over 2D. We discuss design recommendations based on usage patterns and participant comments, and plans for further research.